Impaired oscillometric arterial stiffness parameters in patients with coronary artery ectasia - Alaa Quisi; Gökhan Alıcı; Samir Allahverdiyev; Ömer Genç; Ahmet Oytun Baykan; Süleyman Özbiçer; Mevlüt Koç (KARE Publishing, 2018)
Objective: The aim of this study was to investigate the oscillometric measurements of the elastic properties of the aorta in patients with isolated coronary artery ectasia (CAE). Methods: This study included 137 patients (92 men and 45 women; mean age: 60.8+-11.7 years) who underwent coronary angiography to investigate ischemic heart disease. The patients were divided into 3 groups; the first group consisted of 51 patients with CAE, the second group comprised 36 patients with coronary artery disease (CAD), and the third group was made up of 50 patients with normal coronary arteries. Aortic stiffness (AS) measurements, including pulse wave velocity (PWV) and augmentation index (AIx), were measured using the oscillometric method. Results: The mean PWV was significantly higher in the CAE group compared with the CAD and control groups (9.1+-2.3 vs. 8.2+-1.3 and 8.0+-1.6; p=0.008), whereas the median AIx was significantly lower in the CAE group compared with the CAD and control groups (10.0% [-3.0-63.0] vs. 15.5% [-2.0-57.0] and 21.5% [-1.0-45.0]; p=0.010). Multinomial logistic regression analysis demonstrated that gender, hypertension, high-density lipoprotein cholesterol level, PWV, and AIx were independently associated with CAE. Conclusion: The oscillometric elastic properties of the aorta, including PWV and AIx, are impaired in patients with CAE.